I is for innocent eaudiobook - Grafton, Sue (Kinsey Millhone, 2007)
A Kinsey Millhone mystery. . . Fired by the insurance agency for whom she investigates, Kinsey is forced to take on a last-minute murder investigation in which the ex-husband of a murdered artist claims that David Barney, her current husband, is guilty as sin. Barney gets to Kinsey and insists he's innocent. But if he is, who's guilty? In trying to learn who's been getting away with murder, Kinsey may be courting her own....